An incomplete form of anti-ganglioside antibody-positive Miller Fisher syndrome after an Epstein-Barr virus infection: A case report. Issue 5 (5th February 2021) - Chang, Le; Xiong, Jing; Xue, Yuying; Wang, Jie; Zhu, Xurong; Zheng, Xuejiao; Gao, Xiaoyu; Yan, YuE; Hao, Jiaduo; Zhao, Hehuan; Di, Zhengli
Abstract: Rationale: The Miller Fisher syndrome (MFS) is an acute polyradiculoneuritis regarded as an uncommon clinical variant of the Guillain-Barre syndrome (GBS). It is characterized by the clinical triad of ophthalmoplegia, ataxia, and areflexia. The diagnosis of MFS is based on clinical presentation, presence of albuminocytologic dissociation in the cerebrospinal fluid (CSF), and normal brain imaging results. The presence of anti-ganglioside antibodies (GQlb) in the serum is helpful for the diagnosis. A history of upper respiratory tract infection or diarrhea 3 days to 6 weeks before the onset of MFS is common. However, there are some patients with atypical manifestations who are difficult to diagnose. Here, we present an incomplete form of MFS where antibodies against GQ1b were detected in the serum following an Epstein Barr virus (EBV) infection. Patient concerns: A 77-year-old Chinese woman was admitted to the hospital with acute diplopia and right blepharoptosis. She had a history of mild upper respiratory tract infection 2 weeks ago. In 1 week, the symptoms rapidly progressed into bilateral ophthalmoplegia and hyporeflexia of the limbs without ataxia. CSF analysis on the third day after onset was normal, without albuminocytologic dissociation. EBV immunoglobulin G (IgG) antibodies were detected in the CSF. GQ1b and GD1b IgG antibodies were positive in the serum and negative in the CSF. No responsible lesion was found on brain imaging examination. Diagnoses: In accordance with the progressive bilateral ophthalmoplegia and hyporeflexia, the history of upper respiratory tract infection, the detection of EBV and GQ1b antibodies, and the negative brain imaging examination, the diagnosis of MFS was confirmed. Interventions: The patient was administered intravenous immunoglobulin for 5 days. Outcomes: She had a favorable outcome after treatment. At the 6-week follow-up, bilateral ocular movement limitation and tendon reflexes had recovered. Lessons: The diagnosis of MFS can be challenging, especially when encountered with incomplete symptoms and normal CSF results. Attention should be paid to the presence of anti-GQ1b IgG antibodies when the clinical manifestations are incomplete. Furthermore, EBV primary infection could be associated with MFS and considered a potential causative agent.